Impact of time after fire on post-fire seismic behavior of RC columns - Demir, Ugur; Goksu, Caglar; Binbir, Ergun; Ilki, Alper (Elsevier BV, 2020)
Abstract Autogenous recovery after fire exposure is known to be effective on the behavior of reinforced concrete structural members. This is substantially attributed to the variations on the residual mechanical properties of concrete as a function of time after fire. For the first time, in this study, an experimental study was carried out to examine the impact of time after fire on (i) post-fire behavior of small-scale specimens (cubes and cylinders), (ii) seismic behavior of full-scale flexure-controlled reinforced concrete columns. Outcomes of the post-fire seismic test results were investigated on a total of four columns one of which was an unheated reference specimen, whereas the other three were heated for 90 minutes following the ISO-834 fire curve. Seismic tests were carried out on fire exposed columns 30, 60 or 360 days after fire exposure. The test results indicated that 90 minutes of fire exposure caused a reduction in lateral load capacity, ductility and stiffness of the columns with respect to the unheated column. On the other hand, impact of time after fire exposure on residual lateral load capacity and ductility of the columns was found to be limited while the column subjected to seismic test 30 days after fire exposure exhibited less stiff behavior with respect to the columns tested later. Furthermore, an analytical study is conducted for the prediction of seismic behavior of reinforced concrete columns after fire exposure considering the variations in residual properties of concrete by time, and the proposed model is found to be in good agreement with the test results.